The Effect of Frequency Acoustic Stimulation Sound on Intrauterine Weakening of Pregnant Sheep - Suherman, Djamil; Joewono, Hermanto Tri; Sardjana, I Komang Wiarsa (KnE Life Sciences, 2017)
Research to determine changes in intrauterine sound pressure in pregnant sheep after administration acoustic stimulation outside of the abdominal wall at some frequency sounds. The study was conducted at the Animal Hospital of Veterinary Faculty of Airlangga University. Pre test experimental design with pre- and post-test one group to assess intra-uterine sound pressure changes. The study was conducted at two lambs pregnant aterm after acoustic stimulation at a distance of 10 cm from the surface of the abdominal wall to the sound pressure 80,85,90,95 and 100 decibels and sound frequency of 31.5, 63, 125, 250, 500, 1000, 2000, 4000, 6000 and 8000 hertz. The results showed that the difference between the sound pressure outside of the abdominal wall with intrauterine sound pressure on both the pregnant sheep by an average of 16.7570 ± 8.0797 decibels. This shows their weakening sound after passing through the abdominal wall and the uterine wall. By using a paired t-test, this weakening statistically significant. At frequencies from 31.5 to 1000 hertz weakening values from 5.2 to 17.1 decibels while in 2000-8000 hertz frequency weakening value of 20.2 to 30.8 decibels. The conclusion that the stimulation of noise from outside the walls of the abdomen weakening sound after penetrating the abdominal wall and the uterine wall. Weakening occur at every level of sound pressure and at every level of a given frequency. Weakening value becomes greater at frequencies above 1000 hertz. Keywords: weakening, sound pressure, sound frequency, pregnant sheep.